1992
DOI: 10.1007/bf00039917
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of embryogenic callus and high protoplast yielding suspension cultures of sugarcane (Saccharum spp. hybrids)

Abstract: For 18 sugarcane cultivars, four,.distinct callus types developed on leaf explant tissue cultured on modified MS medium, but only Type 3 (embryogenic) and Type 4 (organogenic) were capable of plant regeneration. Cell suspension cultures were initiated from embryogenic callus incubated in a liquid medium. In stage one the callus adapted to the liquid medium. In stage two a heterogeneous cell suspension culture formed in 14 cultivars after five to eight weeks of culture. In stage three a homogeneous cell suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
7

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 17 publications
5
35
0
7
Order By: Relevance
“…Regarding the results described in the literature and here observed the morphological variations of callus and shoot regeneration pathways are frequently reported in studies of in vitro shoot induction of sugarcane. The association of organogenic and embryogenic callus on the same sugarcane explant and the plant regeneration through indirect organogenesis from friable callus has been described in some studies (GNANAPRAGASAM & VASIL, 1992;TAYLOR et al, 1992;RODRIGUEZ et al, 1995). In another study, FRANKLIN et al (2006) reported the shoots induction of sugarcane from globular structures associated with the original explant and suggest that somatic embryos in globular stage may lead shoots induction from indirect organogenesis in the presence of cytokines, confirming the results observed here.…”
Section: Histological Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the results described in the literature and here observed the morphological variations of callus and shoot regeneration pathways are frequently reported in studies of in vitro shoot induction of sugarcane. The association of organogenic and embryogenic callus on the same sugarcane explant and the plant regeneration through indirect organogenesis from friable callus has been described in some studies (GNANAPRAGASAM & VASIL, 1992;TAYLOR et al, 1992;RODRIGUEZ et al, 1995). In another study, FRANKLIN et al (2006) reported the shoots induction of sugarcane from globular structures associated with the original explant and suggest that somatic embryos in globular stage may lead shoots induction from indirect organogenesis in the presence of cytokines, confirming the results observed here.…”
Section: Histological Analysissupporting
confidence: 89%
“…The somatic embryogenesis induction has been obtained from explants of sugarcane inoculated in medium supplemented with various auxin types (HO & VASIL, 1983;FITCH & MOORE, 1990;BRISIBE et al, 1994). In other study, TAYLOR et al (1992) described the induction of organogenic and embryogenic callus in 18 cultivars, as well as to obtain cell cultures in suspension. Plant regeneration from embryogenic callus obtained from immature leaves was observed by DIBAX et al (2011), NIEVES et al (2008, VICKERS et al (2005) and BLANCO et al (1997) and using MS medium (MURASHIGE & SKOOG, 1962) supplemented with 2,4 dichlorophenoxyacetic acid (2,4-D) and LIU (1993), using different combinations of 2,4-D, kinetin (KIN), benzylaminopurine (BAP) and calcium pantothenate.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors (Jimenez et al, 1991;Lorenzo et al, 2001;Lourens. & Martin 1987;Taylor et al, 1992) indicate that such differences disappear during the course of field growth and the first clonal multiplication, as observed in our experiments. Bioplantas for mass production of in vitro sugarcane plants by means of somatic embryogenesis.…”
Section: Stability Assessmentsupporting
confidence: 68%
“…A indução de calos embriogênicos já foi obtida em explantes de cana-de-açúcar inoculados em meio suplementado com diversos tipos de auxina (Ho & Vasil 1983, Fitch & Moore 1990, Brisibe et al 1994. Taylor et al (1992) descreveram a indução de calos organogênicos e embriogênicos em 18 cultivares, bem como a obtenção de culturas de células em suspensão. A regeneração de plantas a partir de calos embriogênicos obtidos através do cultivo de explantes de inflorescência imatura foi observada por Blanco et al (1997) em meio suplementado por 2,4-D (ácido 2,4 diclorofenoxiacético) e por Liu (1993), utilizando diferentes combinações de 2,4-D, cinetina, 6-BA (6-benzilaminopurina) e pantetonato de cálcio.…”
Section: Introductionunclassified